An Evaluative Study on Sidoarjo Mud Flow after Phytoremediation Treatment in Milk Fish (Chanos Chanos) Liver - Dewi Hidayati (IPTEK The Journal for Technology and Science, 2010)
A sudden discharge of Sidoarjo mud flow into the water bodies would disturb aquatic biota, the fisheries culture. The aim of this research is to evaluate the availability of phytoremediated water of Sidoarjo mud flow (abbreviated: pwmf) as a milkfish culture media using liver histological approach. After two weeks acclimatization period, the juvenile and adult of milkfish were exposed the pwmf at the sub lethal concentration and an acute static bioassay at 96 hours. Control fishes were reared in the artificial brackish water. Each treatment of pwmf exposure was done in three replicates. After exposure, the liver fishes were removed and histologically processed using paraffin method and HE staining. Histopathology change was assessed semi quantitative scoring. The result of the histological analyses suggested the liver pathological features such as vacuolation of hepatocytes, the loss of sinusoid integrity from mild to severe occurrence and necrosis.